Dampak Pandemi Covid-19 terhadap Tren Pelayanan KIA di Kabupaten Tangerang Tahun 2020: Dampak Pandemi Covid-19 terhadap Tren Pelayanan KIA di Kabupaten Tangerang Tahun 2020 - Herawati Herawati; Trini Sudiarti (NERSMID : Jurnal Keperawatan dan Kebidanan, 2022)
The Indonesian government has declared the COVID-19 outbreak a national disaster on March 14, 2020 The COVID-19 pandemic has had an impact on maternal and child health services. The decline in antenatal care visits and health services for infants and toddlers occurred during the COVID-19 pandemic as a result of policies such as Large-Scale Social Restrictions (PSBB) during the pandemic. The research method uses a mixed methods approach with a deductive-sequential design. The population in this study were all mothers, infants and children. toddlers who are in Tangerang district while the samples in this study are mothers, infants and toddlers whose data is available on the Recover Covid dashboard. The results of the study show indicators of Maternal and Child Health programs that have been negatively affected by the COVID-19 pandemic, including K1 and K4 coverage, children under five being monitored for growth and development, IDL and maternal mortality. Suggestions from this study need to arrange a village visit schedule, optimize referral hospitals for maternity patients with COVID-19, improve delivery facilities and infrastructure for mothers with COVID-19 and support APBD from local governments